Eski Osmanlıcada ve Türkmencede "İdük" Yapısı - Öztürk, Rıdvan (Kitabevi, 2003)
"Idük" morpheme that was widely used during Old Ottoman Turkish, still exists merely in an archaic usage in present Turkey Turkish. This morpheme that lost its using frequency, is faced in Turkoman Turkish actively. In this paper beginning from Old Ottoman, the initial period of written languages of Oghuz group, Turkey Turkish and Turkoman Turkish that are branchs of written languages of Oghuz group were considered.
"Idük" Morpheme in Old Ottoman Turkish and Turkoman Turkish
Keywords: Turkoman Turkish; Old Anatolian Turkish; Morfem of "idük"; Morphologie